Analisis dan Perancangan Sistem Informasi Perpustakaan Digital Berbasis Web - Subekti, Putri; Pratama, Anton (Journal of Data Science and Information Systems, 2024)
The design of a digital library information system involves creating a framework and infrastructure that enables efficient management and access of library information through digital platforms. Problems that are often faced by libraries are related to challenges in keeping up with the development of information technology, as well as facing competition with digital information sources available online. This stage of design includes identifying user needs, mapping library business processes, selecting appropriate technologies, and developing intuitive interfaces for users. In addition, the design also includes a database structure for storing collection information, integration with library management systems, and the implementation of features such as search, borrowing, returning, and user account management. With careful design, digital library information systems can improve the accessibility and quality of library services for users as a whole. The results of system testing using blackbox testing show results of 100% that the system has successfully passed all well. This indicates that the system has met all established functional specifications, provided appropriate responses to various inputs, and met quality standards and user needs. This conclusion provides confidence that the system is ready for implementation and use by end users, with a high level of reliability and minimal risk of errors.